The prevalence of soil-transmitted helminths infection and its association with anaemia among refugee school children in the Klang Valley, Malaysia - Ibrahem Alaribi, Fatma; Unyah, Ngah Zasmy; Misni, Norashiqin; Masri, Siti Norbaya; Osman, Malina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Soil-transmitted helminths (STHs) are considered one of the neglected parasitic diseases that cause major health problems and other related complications. The aim of this study was to determine the prevalence of STHs and anaemia among school children of little-known refugee communities in Malaysia. Methods: A cross-sectional study was conducted among 148 refugee school children in the Klang Valley, Malaysia, from 2017 to 2019. Data were collected using a questionnaire, in addition to haemoglobin testing while faecal samples were screened for STHs eggs using the formalin-ether concentration technique. Results: The result showed that the prevalence of STHs in this study was 37.2%. Trichuris trichiura infection was the most prevalent (46.4%) followed by Ascaris lumbricoides (44.9%) and hookworms (8.7%). About 37.8 % of the respondents were found to be anaemic. Binary logistic regression showed significant infection with STHs complicated with anaemia (AOR: 3.67, 95 % CI 1.595-8.5). Conclusion: The evidence from this study suggests proper and strategic interventions to reduce morbidity. An alternative and efficient system is needed to provide the schoolchildren with basic care for sanitation and health provision. It is recommended that voluntary clinics provided by non-government organisations focus on counselling and advice on personal hygiene of the children.